P167 Characterisation of tuberculous mediastinal lymphadenopathy on CT and correlation with biomarkers and chest radiograph findings. (16th November 2010) - Singanayagam, A; George, P; Connell, D; Kaneria, S; Dhariwal, J; Molyneaux, P; Wickremasinghe, M; Lalvani, A; Wright, A; Kon, O M
Abstract : Introduction: The aim of this study was to characterise the anatomical pattern of mediastinal lymphadenopathy on CT in active tuberculosis (TB) and assess correlation with biomarkers and chest radiograph (CXR) findings. Methods: We conducted a retrospective analysis of patients treated for active TB with mediastinal lymphadenopathy at a tertiary centre between January 2007 and May 2009. CT scans performed prior to commencement of therapy were reviewed by two radiologists to assess for pathologically enlarged lymph nodes (LN) (short axis diameter >1.0 cm) at each of the LN stations defined by the International Association for the Study of Lung Cancer (IASLC). Results: 55 patients were included in the study. 56.3% of enlarged LNs were right sided, 32.9% were in central LN groups and 10.8% were left sided. 40.0% of patients had evidence of necrosis within LNs. The most frequently occurring enlarged LNs were in the subcarinal (level 7; 81.8% of patients), right lower paratracheal (level 4R; 58.2%) and right hilar (level 10R; 52.7%) stations. The Abstract P167 Table 1 shows correlation of biomarkers and CXR abnormalities with extent of LN involvement on CT. Results are displayed as % group or median (IQR). There were 49.1% with a normal CXR. In this subgroup, ESR and Globulin levels also correlated with extent of LN involvement on CT. The median (IQR) LN involvement stratified by ESR levels was: 2 (1–2), 2 (1–2.8) and 5 (4–5) for ESR ≤15, ESR 16–49 and ESR >49 mm/h, respectively (p=0.039). The median (IQR) LN involvement stratified by Globulin levels was: 2 (1–3), 2 (2–4.8) and 5 (2.8–5.3) for Globulin ≤35, Globulin 36–45 and Globulin>45 g/l, respectively (p=0.048). Conclusion: Tuberculous mediastinal lymphadenopathy on CT is characterised by a specific anatomical pattern with predominance of right sided LNs and more frequent involvement of particular LN stations. A large proportion of patients with pathologically enlarged LNs on CT have normal CXRs. Biomarkers such as ESR and globulin levels correlate with extent of LN involvement on CT.